Professor, Dr. phil. E. Rostrup.Født den 28. Januar 1831. — Død den 16. Januar 1907. - Hertel, H. (Tidsskrift for Landøkonomi, 2018)
Professor, Dr. phil. E. Rostrup.Født den 28. Januar 1831. — Død den 16. Januar 1907.